ML-11 Tirabrutinib treatment for recurrent or refractory PCNSL. (6th December 2021) - Ohka, Fumiharu; Yamaguchi, Junya; Motomura, Kazuya; Aoki, Kosuke; Nishikawa, Tomohide; Kibe, Yuji; Yamazaki, Shintaro; Natsume, Atsushi; Saito, Ryuta
Abstract: Since 2020, tirabrutinib which is a Bruton's tyrosine kinase (BTK) inhibitor has been available for recurrent or refractory PCNSL cases. The number of studies reporting efficiency and adverse effect of tirabrutinib treatment for recurrent or refractory PCNSL has been limited yet. In this study, we investigated clinical course of eight refractory or recurrent PCNSL cases treated with tirabrutinib in our institute. Eight PCNSL cases treated with tirabrutinib included four recurrent cases and four refractory cases. Five cases obtained CR or PR after 26.8 days administration of tirabrutinib and other two cases also exhibited obvious improvement of clinical symptoms after 23.5 days administration of tirabrutinib. Among three cases exhibiting intraocular lesions, two cases revealed improvement of visual dysfunction and the other case obtained SD status of intraocular lesion. The most frequently found adverse effect was the skin rash. CTCAE grade 2 (n=2) or 3 (n=2) rash was found after mean 16 days or 94 days of tirabrutinib administration, respectively. Two cases with grade 3 rash could start taking the low-dose tirabrutinib after improvement of rash. Althouth one case experienced shingles, no other case experienced serious adverse effects. Although adverse effect of rash was frequently found, we could obtain high response rate of tirabrutinib treatment for recurrent or refractory PCNSL cases. We need to establish quantitative assessment method for analysis of treatment response of tirabrutinib for intraocular lesions.